Prediction of neuroblastoma cell response to treatment with natural or synthetic retinoids using selected protein biomarkers - Dobrotkova, Viera; Chlapek, Petr; Jezova, Marta; Adamkova, Katerina; Mazanek, Pavel; Sterba, Jaroslav; Veselska, Renata (PloS one, 2019)
Although the administration of retinoids represents an important part of treatment for children suffering from high-risk neuroblastomas, approximately 50% of these patients do not respond to this therapy or develop resistance to retinoids during treatment. Our study focused on the comparative analysis of the expression of five genes and corresponding proteins (DDX39A, HMGA1, HMGA2, HOXC9 and PBX1) that have recently been discussed as possible predictive biomarkers of clinical response to retinoid differentiation therapy. Expression of these five candidate biomarkers was evaluated at both the mRNA and protein level in the same subset of 8 neuroblastoma cell lines after treatment with natural or synthetic retinoids. We found that the cell lines that were HMGA2-positive and/or HOXC9-negative have a reduced sensitivity to retinoids. Furthermore, the experiments revealed that the retinoid-sensitive cell lines showed a uniform pattern of change after treatment with both natural and sensitive retinoids: increased DDX39A and decreased PBX1 protein levels. Our results showed that in NBL cells, these putative protein biomarkers are associated with sensitivity or resistance to retinoids, and their endogenous or induced expression can distinguish between these two phenotypes.
Keywords: Drug Resistance, Neoplasm; pre-B-buněčný leukemický transkripční faktor 1; isotretinoin; proliferace buněk; Nervous System Neoplasms; Tissue Fixation; Fenretinide; Female; Infant; HMGA1a Protein; dítě; předškolní dítě; protein HMGA2; novorozenec; Bexarotene; Cell Line, Tumor; Tretinoin; ženské pohlaví; mladý dospělý; tretinoin; Adolescent; fenretinid; lidé; Infant, Newborn; Antineoplastic Agents; protinádorové látky; Paraffin Embedding; chemorezistence; homeodoménové proteiny; Pre-B-Cell Leukemia Transcription Factor 1; DEAD-box RNA-helikasy; nádory nervového systému; Male; biomarkery farmakologické; kojenec; bexaroten; Child, Preschool; zalévání tkání do parafínu; Young Adult; Cell Proliferation; Homeodomain Proteins; Biomarkers, Pharmacological; Neuroblastoma; Isotretinoin; Child; neuroblastom; mužské pohlaví; HMGA2 Protein; protein HMGA1A; mladiství; fixace tkání; nádorové buněčné linie; DEAD-box RNA Helicases; Humans